Thomas Truxtun papers - Truxtun, Thomas, 1755-1822.
Correspondence, affidavits, certificates, receipts, and other documents drawn up by the crew of the frigate Constellation concerning the collection of prize money due them from prizes captured by that ship. Also includes letters from Truxton to Thomas Tingey, commandant of the Washington Navy Yard, regarding naval matters and Aaron Burr's trial for treason. A typewritten transcript of the letters contains annotations and an index.
Naval officer.
Collection material in English.
Keywords: Burr, Aaron, -- 1756-1836 -- Trials, litigation, etc; Tingey, Thomas, -- 1750-1829 -- Correspondence; United States. -- Navy; Constellation (Frigate); Naval officers